Influence of N₂ partial pressure on the microstructure, hardness, and thermal stability of CrZrSiN nanocomposite coatings - Kim, K.S.; Kim, H.K.; La, J.H.; Kim, K.B.; Lee, S.Y. (Сверхтвердые материалы, 2016)
The effects of N₂ partial pressure in the unbalanced magnetron sputtering process on the microstructure, hardness, and thermal stability of the CrZrSiN nanocomposite coating were investigated. A